Caregiver-child discrepancy in healthcare transition readiness and its associations - Yunzhen Huang; Eugene Maung; Stephen R. Hooper; Chad Coltrane; Maria Díaz-González de Ferris (Health Care Transitions, 2025)
Purpose: To explore caregiver-child discrepancy in healthcare transition (HCT) readiness and its association with demographic variables, anxiety, and health services utilization in children and adolescents with chronic health conditions. Methods: This cross-sectional study surveyed 214 caregiver-child dyads recruited from a therapeutic camp in the Southeastern United States. Children and adolescents aged 7–17 years and their caregivers completed the STARx Questionnaire to assess HCT readiness. Additionally, children rated their anxiety using the PROMIS-Anxiety scale, and caregivers reported their child’s past-year health services utilization. Paired t-tests were used to examine the caregiver-child discrepancies in HCT readiness. Correlation analyses and linear regression were used to explore factors associated with caregiver-child discrepancies in HCT readiness. Results: No statistically significant discrepancies were identified at the full-scale and subscale levels of the STARx Questionnaire. However, single-item level analysis showed caregiver-child discrepancies in their perception of the child’s medication adherence and disease knowledge. Caregivers generally rated children’s HCT readiness higher than children did themselves, particularly in younger children and those diagnosed at a younger age. Higher caregiver ratings were correlated with greater child anxiety. Conclusion: This study revealed gaps in caregiver-child perceptions of the child’s HCT readiness. Addressing these gaps through collaborative communication, shared decision-making, and targeted interventions may improve the HCT process and outcomes. Additionally, this study showed that greater caregiver ratings were linked to younger age, younger age at diagnoses, and elevated child anxiety, calling for early, effective interventions for transition planning to mitigate differences in caregiver-child ratings and facilitate HCT.